1990
DOI: 10.1165/ajrcmb/3.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mucin Synthesis and Secretion in Human Tracheobronchial Epithelial Cells Grown in Culture

Abstract: The effects of culture conditions on growth and differentiation of human tracheobronchial epithelial (HTBE) cells have been defined. Epithelial cells were dissociated from tissues by protease treatment and were plated on tissue culture dishes in F12 medium supplemented with insulin, transferrin, epidermal growth factor, hydrocortisone, cholera toxin, bovine hypothalamus extract, and retinol. HTBE cells did not express any mucociliary function (ciliogenesis or mucin secretion) on tissue culture plastic, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 20 publications
(23 reference statements)
2
56
0
Order By: Relevance
“…This was an unexpected ®nding because retinoids inhibit the growth of a variety of malignant cell lines (Amos and Lotan, 1991;Gudas et al, 1994;Lotan, 1995), and we showed that several other NSCLC cell lines were more sensitive to ATRA in serum-free than in serum-containing medium. Similar to our ®nding, the growth of normal human tracheobronchial epithelial cells (Lechner et al, 1982;Wu et al, 1990) and of human lung adenocarcinoma cells (Yang et al, 1992) was enhanced by low ATRA concentrations (510…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was an unexpected ®nding because retinoids inhibit the growth of a variety of malignant cell lines (Amos and Lotan, 1991;Gudas et al, 1994;Lotan, 1995), and we showed that several other NSCLC cell lines were more sensitive to ATRA in serum-free than in serum-containing medium. Similar to our ®nding, the growth of normal human tracheobronchial epithelial cells (Lechner et al, 1982;Wu et al, 1990) and of human lung adenocarcinoma cells (Yang et al, 1992) was enhanced by low ATRA concentrations (510…”
Section: Discussionsupporting
confidence: 84%
“…yet inhibited at high concentrations (10 76 M) (Wu et al, 1990;Geradts et al, 1993). The growth of SCLC cell lines was inhibited by 13-cis-RA concentrations 410 76 M in serum-free medium but not in the presence of serum and 2% bovine serum albumin (BSA), which was identi®ed as the major serum component responsible for binding radiolabeled ATRA, reversed the growth inhibitory eect of 13-cis-RA (Avis et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were collected only from patients without known respiratory tract diseases. Primary cultures derived from these airway tissues have been established before (37,38). Protease-dissociated TBE cells were plated on a collagen gel substratum-coated Transwell (Corning Costar, Corning, NY) chamber (25 mm) at 1-2 ϫ 10 4 cells/ cm 2 , in a Ham's F12/DMEM (1:1) supplemented with insulin (5 g/ml), transferrin (5 g/ml), epidermal growth factor (10 ng/ml), dexamethasone (0.1 M), cholera toxin (10 ng/ml), bovine hypothalamus extract (15 g/ ml), BSA (0.5 mg/ml), and all-trans-retinoic acid (30 nM).…”
Section: Cell Culture From Human and Mouse Airway Tissuesmentioning
confidence: 99%
“…NHBE cells were maintained in air-liquid interface culture for full mucociliary differentiation. 20,21 The immortalized NHBE cell line HBE1 was cultured under the same conditions as NHBE cells. 19 Tracheobronchial tissue sections from patients with asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (CF) and from patients with no obvious airway diseases were obtained with consent from the University of Miami Medical Center.…”
Section: Human Airway Tissue Sources and Culture Conditionsmentioning
confidence: 99%